A pilot integrative genomics study of GABA and glutamate neurotransmitter systems in suicide, suicidal behavior, and major depressive disorder. Issue 3 (19th February 2016) - Yin, Honglei; Pantazatos, Spiro P.; Galfalvy, Hanga; Huang, Yung‐yu; Rosoklija, Gorazd B.; Dwork, Andrew J.; Burke, Ainsley; Arango, Victoria; Oquendo, Maria A.; Mann, Joseph John
Abstract : Gamma‐amino butyric acid (GABA) and glutamate are the major inhibitory and excitatory neurotransmitters in the mammalian central nervous system, respectively, and have been associated with suicidal behavior and major depressive disorder (MDD). We examined the relationship between genotype, brain transcriptome, and MDD/suicide for 24 genes involved in GABAergic and glutamatergic signaling. In part 1 of the study, 119 candidate SNPs in 24 genes (4 transporters, 4 enzymes, and 16 receptors) were tested for associations with MDD and suicidal behavior in 276 live participants (86 nonfatal suicide attempters with MDD and 190 non‐attempters of whom 70% had MDD) and 209 postmortem cases (121 suicide deaths of whom 62% had MDD and 88 sudden death from other causes of whom 11% had MDD) using logistic regression adjusting for sex and age. In part 2, RNA‐seq was used to assay isoform‐level expression in dorsolateral prefrontal cortex of 59 postmortem samples (21 with MDD and suicide, 9 MDD without suicide, and 29 sudden death non‐suicides and no psychiatric illness) using robust regression adjusting for sex, age, and RIN score. In part 3, SNPs with subthreshold (uncorrected) significance levels below 0.05 for an association with suicidal behavior and/or MDD in part 1 were tested for eQTL effects in prefrontal cortex using the Brain eQTL Almanac (www.braineac.org ). No SNPs or transcripts were significant after adjustment for multiple comparisons. However, a protein coding transcript (ENST00000414552) of the GABA A receptor, gamma 2 (GABRG2) had lower brain expression postmortem in suicide ( P = 0.01) and evidence for association with suicide death ( P = 0.03) in a SNP that may be an eQTL in prefrontal cortex (rs424740, P = 0.02). These preliminary results implicate GABRG2 in suicide and warrant further investigation and replication in larger samples. © 2016 Wiley Periodicals, Inc.